Kajian Ikan Terumbu Karang dengan persentase Tutupan Terumbu Karang Hidup di Kawasan Konservasi Perairan Tanjung Labu Kabupaten Bangka Selatan - Jemi Ferizal; Wahyu Adi; Adisti Hafizah; Fera Angelia; Fajar Hidayatullah Ramadhani; Ervansyah Maulana; Hendi Hendi; Rama Kristian Fitriyansah; Nadya Syasri Aryani; Jongki Arifandi; Terisna Terisna; Juliana Erika Putri (Fakultas Kelautan dan Perikanan Universitas Udayana, 2023)
Community activities in Tanjung Labu waters include loading and unloading, fishing, coral reef mining, and others. Coral reefs and fish associated are directly affected by these activities. This research was carried out on June 2023 in Tanjung Labu Waters, Lepar District, South Bangka. The aimed of the research was to determined the number of individual indicator, major and target fish and the relationship between live coral reef cover and biomass. The coral reef data collection method uses UPT (Underwater Photo Transect), and coral reef fish use UVC (Underwater Visual Census). The results of the percentage of coral reef cover are in the moderately damaged category, the abundance of coral reef fish is in the very rare category. The relationship between the percentage of live coral reef cover and the abundance of fish in the indicator, major, target categories and coral reef fish biomass, had a positive relationship and was quite strong to strong. The relationship between coral reef fish abundance and biomass was perfectly positive with a very strong correlation coefficient. Factors that influenced the relationship between the percentage of live coral reef cover and the abundance and biomass of coral reef fish were food availability and anthropogenic activities. The relationship between abundance and biomass of coral reef fish was related to length and high abundance. Efforts to manage the Tanjung Labu Village conservation area on Lepar Island, reduce anthropogenic activities, increase education regarding applicable regulations, strengthen supervision and law enforcement (institutional) and rehabilitate coral reefs.